Low gestational age at birth and difficulties in school-A matter of 'dose'. - Rikke Wiingreen (PLoS ONE, 2018)
OBJECTIVES:Several studies suggest a relationship between gestational age at birth and risk of school difficulties. Our study aimed to investigate the association between the entire range of gestational ages and significant school difficulties measured as 1) More than nine hours per week special educational support and 2) Failing to complete compulsory school. METHODS:A population-based register study including all children attending the Danish compulsory school in 2015/2016 and all live-born infants born in Denmark from 1992 to 1997. Data were collected and linked using multiple registers held by Statistic Denmark. Multiple logistic regression analyses were used to estimate the association between gestational age and significant school difficulties, adjusted for explanatory variables. RESULTS:For measurement 1) "Special educational support" 615,789 children entered the analyses after exclusion of those with missing neonatal data. The risk of special educational support increased gradually across the entire range of gestation from 40 to ≤24 weeks: The adjusted odds ratio was 1.07 (95% confidence interval 1.03-1.12) at 39 weeks of gestational and 6.18 (95% confidence interval 5.17-7.39) at gestational ages < 28 weeks. For measurement 2) "Failing to complete compulsory school" the cohort consisted of 374,798 children after exclusion of those who died, had emigrated and/or had missing neonatal data. The risk of failing to complete compulsory school increased across the entire range of gestational ages: The adjusted odds ratio was 1.07 (95% confidence interval 1.04-1.10) at 39 weeks of gestation and 2.99 (95% confidence interval 2.41-3.71) at gestational ages < 28 weeks. In both sets of analyses GA = 40 weeks was used as reference. CONCLUSIONS:We confirm a clear association between the degree of prematurity and significant school difficulties across the entire range of gestational ages from ≤ 24 to 40 weeks.